First-Principle Investigation of La0.7Ba0.3Mn(1-x)FexO3 Structural Properties Using CASTEP - Sitti Ahmiatri Saptari; Sarah Aulia; Ryan Rizaldy; Anugrah Azhar (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2023)
We conducted first-principles Density Functional Theory (DFT) calculations using the CASTEP software package to investigate the crystal structure and mechanical properties of Fe3+-doped La0.7Ba0.3MnO3 material at the Mn3+ site, with doping concentrations ranging up to 50%. Through geometry optimization, we simulated the X-ray diffraction (XRD) pattern. We observed that the doping of Fe did not result in a shift in the peak positions of the diffraction pattern. However, it led to an increase in intensity at the [012] peak and the splitting of peaks [104] and [110]. Regarding the mechanical properties, we examined the elastic constants and observed a reduction in the Bulk, Shear, and Young's modulus values. The Shear and Bulk modulus and Poisson's ratio indicated that La0.7Ba0.3Mn(1-x)FexO3 becomes less ductile with increased Fe3+ doping content. Furthermore, we performed calculations for the Debye temperature, which revealed a decrease in the thermal conductivity of the La0.7Ba0.3Mn(1-x)FexO3 material.